Pengembangan Aplikasi Panduan KB Smart Kontrasepsi Hormonal pada Ibu Hamil - Wulan Wulan; Ansar Suyuti; Sri Ramadany (Poltekkes Kemenkes Palu, 2022)
Introduction: Advances in technology can help create new breakthroughs in providing information about family planning through a more efficient android-based contraceptive application that is useful for pregnant woman. The purpose of this study was to analyze the effect of using the smart hormonal contraception KB guide application on increasing knowledge of pregnant women. Methods: Quasi-experimental research method with a two-group pre-test and post-test design. The sample of this study involved 94 pregnant women with the sampling technique using purposive sampling. The respondents of this study were then divided into 2 groups, namely the experimental group and the control group. Data were analyzed using Wilcoxon Signed Rank Test and Mann Whitney statistical analysis. Result: that the significant use of the hormonal contraceptive smart KB application can increase the knowledge of pregnant women about hormonal contraception by 72.3% (p-value 0.000) with good category. It also shows that there is a more significant increase in knowledge among pregnant women compared to pregnant women, which is only 44.7% (p-value 0.000) in the sufficient category. Conclusion: The use of the hormonal contraceptive smart KB guide application can significantly increase the knowledge of pregnant women.